2021
DOI: 10.1101/2021.08.25.457363
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phosphorylated tau fluid biomarker sites recognize earlier neurofibrillary tangle maturity levels in the postmortem Alzheimer’s disease brain

Abstract: Alzheimer’s disease (AD) biomarkers have become increasingly more reliable in predicting AD pathology. While phosphorylated tau fluid biomarkers have been studied for over 20 years, there is a lack of deep characterization of these sites in the postmortem brain. Neurofibrillary tangle-bearing neurons, one of the major neuropathologic hallmarks of AD, undergo morphologic changes that mature along a continuum as hyperphosphorylated tau aggregates. To facilitate interpretation of phosphorylated tau sites as an ea… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 61 publications
3
4
0
Order By: Relevance
“…Our study shows that p-tau217 can be found within NFTs and NTs also containing the p-tau variants p-tau181, 231, 202, 202/205, and 369/404, a finding suggesting that phosphorylation of tau at site Thr217 often occurs at the same time as phosphorylation at other tau sites. This idea is supported, not only by previous studies demonstrating strong correlations between levels of p-tau217 and various p-tau variants in plasma and CSF [4,10,11,19,20] but also by a recently published study showing that p-tau217 can be found in the same early tangle maturation stages as many of the other p-tau variants including p-tau181, 231, 205 [18]. Our study adds to these studies by demonstrating subtle differences in the coverage of p-tau217 immunoreactivity in NFT and NT compared to the other p-tau variants.…”
Section: Discussionsupporting
confidence: 56%
“…Our study shows that p-tau217 can be found within NFTs and NTs also containing the p-tau variants p-tau181, 231, 202, 202/205, and 369/404, a finding suggesting that phosphorylation of tau at site Thr217 often occurs at the same time as phosphorylation at other tau sites. This idea is supported, not only by previous studies demonstrating strong correlations between levels of p-tau217 and various p-tau variants in plasma and CSF [4,10,11,19,20] but also by a recently published study showing that p-tau217 can be found in the same early tangle maturation stages as many of the other p-tau variants including p-tau181, 231, 205 [18]. Our study adds to these studies by demonstrating subtle differences in the coverage of p-tau217 immunoreactivity in NFT and NT compared to the other p-tau variants.…”
Section: Discussionsupporting
confidence: 56%
“…Doing so required optimization of an anti-tau pT217 antibody that can recognize other proteins with the identical epitope, an issue that likely applies to other antibodies directed against tau pT217 . Consistent with prior immunohistological studies of human brain [12, 13], we found that tau pT217 first appears in limbic structure neurons at Braak stages I-II, that its presence in the somatodendritic compartment and neuropil threads increases with disease progression, and that its cellular and subcellular distribution overlaps partially with those of other phospho-tau variants associated with AD and other tauopathies. An immunofluorescence study of aged CVN mice indicates that the tau pT217 distribution in this particular AD model mouse strain is similar to what is seen in mid to late-stage human AD, highlighting the potential utility of CVN mice for further studies of tau pT217 .…”
Section: Discussionsupporting
confidence: 90%
“…Our immunohistological analysis of tau pT217 in human brain yielded results similar to those reported earlier by two other groups [12, 13]. At Braak stage 0 we did not detect any tau pT217 (Supplementary Figure 5), but occasional immunostaining of axons, neuropil threads and neuronal cell bodies was evident by Braak stages I-II (Figure 1), and more widespread by Braak stages III-VI (Figures 2 and 3).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations